Fabrication and characterization of porous silicon by two-step anodization using alternating current photo-assisted electrochemical (ACPEC) etching / Fatimah Zulkifli - Zulkifli, Fatimah (2022)
There are several reliable etching techniques to produce a uniform porous silicon (Si) structure on the semiconductor. Wet etching technique that is commonly used such as metal-assisted electroless etching and direct current photoelectrochemical (DCPEC) etching techniques often produced a non-uniform porous structure. While alternating current photoelectrochemical (ACPEC) etching technique produced a high porosity distribution of porous Si but with shallow pores. Consequently, to further enhance the porous Si structures and properties, a new etching technique, which is a two-step alternating current photo-assisted electrochemical (two-step ACPEC) etching technique was introduced in this research work. In the first step, the Si sample was left immersed in the electrolyte for a few minutes. Then, in the second step, the ACPEC technique was applied. Therefore, this research aims to synthesize the porous structure of porous Si using the two-step ACPEC technique and characterize its structural properties under different etching parameters. The work of this research was divided into three objectives: the formation of porous Si using different etching techniques, crystal orientations, etching durations, and current densities. In the first objective, porous Si samples were etched using DCPEC, ACPEC, and two-step ACPEC etching techniques. The porous Si sample etched using two-step ACPEC etching had the highest pore density and porosity, higher surface roughness in root mean square (RMS), and improvement in the uniformity of pores compared to the other two techniques. This showed that the two-step ACPEC technique improved the structural properties of the porous Si compared to the other two techniques. Therefore, the two-step ACPEC etching technique was used to further study the properties of porous Si in the next objectives. For the second objective, two different crystal orientations of Si, namely Si n(100) and Si n(111), were used to synthesize porous Si using the two-step ACPEC technique. The pores formed on porous Si n(100) consist of a mix of crisscross-shaped and a few square-shaped pores while porous Si n(111) exhibited irregular-shaped pores. On top of that, porous Si n(100) exhibited higher pore density and surface roughness than porous Si n(111). This showed that different crystal orientations of Si affected the properties of porous structures. Then, the Si n(100) was used in the next objectives. In the third objective, porous Si was etched at different etching durations. Porous Si etched for 30 minutes exhibited the highest average pore diameter (429.69 nm), porosity (26.99%), surface roughness in RMS (44.50 nm), pore depth (42.94 nm), and pore density out of all the samples. The Raman spectra result showed an improvement in surface area to volume ratio for all of the porous Si samples compared to the as-grown Si. Hence, it could be inferred that different etching duration affected the formation of pores on porous Si structures and the optimized etching duration obtained from this work was 30 minutes. For the next etching parameter, porous Si samples were etched using the two-step ACPEC etching technique at different current densities. The results showed that as the current density increased, the estimated porosity, pore density, average pore depth and surface roughness value in RMS increased. However, when the current density exceeded above 20 mA/cm2, the estimated porosity decreased significantly along with the average pore depth and surface roughness value in RMS. Therefore, it could be concluded that different current densities strongly affected the porous Si structures. Generally, the research outcomes from all these works show different morphologies can be obtained and altered by the potential of porous Si by varying different etching parameters which are eventually suitable for sensing devices.